Penerapan Metode RAD dalam Merancang Aplikasi Web Proyek PLN UIP Sulbagut - Cleorangga Mandang; David Wuisan; Jeener Mandagi (Program Studi Teknik Informatika, 2020)
Abstract— PLN UIP Sulbagut is a company unit in the sector of electricity construction, this unit carries out the construction control and management of the construction of Generators, Transmissions and Substations. The design of the PLN UIP Sulbagut Project Web Application is a solution in helping the public to know about PLN UIP Sulbagut and its construction projects. The results and discussion here shows the Web Application of the PLN UIP Sulbagut is a media that makes it easy for the public to know about this work unit. This application was developed based on the Rapid Application Development (RAD) model which is one of the systems development methods and is modeled with object-oriented modeling tools that are compatible with the RAD model, the Unified Modeling Language (UML).